Design of a novel compact low specific absorption rate multiple input multiple output antenna for 5G sub-6 GHz terminals - Ennajih, Abdelhadi; Sardi, Azzeddine; Mouzouna, Youssef; Sadik, Mohamed; Errkik, Ahmed (Bulletin of Electrical Engineering and Informatics, 2024)
This investigation presents a new design and analysis of a fourteen elements massive multiple input multiple output (MIMO) compact low specific absorption rate (SAR) antenna system for 5G and beyond terminals. The MIMO antennas are realized for sub-6 GHz LTE-band 46 (5.1-5.8 GHz) long-term evolution 5G wireless communication services. The proposed antenna system is designed on an FR-4 dielectric constant 4.3 substrate consisting of the main board and four sideboards. The radiating elements are developed on the sideboards consisting of a monopole antenna and two metamaterial unit cells, as well as the feed line is designed on the principal board. The overall volume of the proposed structure is 150×80×7.5 mm. Through the use of the metamaterial unit cells, the proposed antennas have been arranged in close proximity without developing a strong mutual coupling. The results obtained were very important in terms of impedance matching, isolation among the antennas, and good gain. Even, the SAR analysis at the operating frequency band of 5.5 GHz proves that the proposed MIMO antenna system satisfies safety standards set for human exposure at the international level. Therefore, the proposed massive MIMO antenna structure is a potential solution for future communication applications.